Prevalence of Anemia and Related Deficiencies in the First Year following Laparoscopic Gastric Bypass for Morbid Obesity - E. O. Aarts; B. van Wageningen; I. M. C. Janssen; F. J. Berends (Hindawi Limited, 2012)
Background. Anemia associated with deficiencies in iron, folic acid, and vitamin B12 are very common after Laparoscopic Roux-en-Y Gastric Bypass (LRYGB) surgery for morbid obesity. This study was conducted to evaluate the prevalence of anemia after LRYGB. Patients and Methods. A total of 377 morbid obese patients were included in our study. All patients underwent a LRYGB. Hematologic parameters were obtained prior to and after surgery on standardized time intervals. Results. Anemia was present in 21 (P=0.02) patients after surgery. Iron, folic acid, and vitamin B12 deficiencies were diagnosed in 66%, 15%, and 50% of patients, respectively. In 86% of patients, anemia was accompanied by one of these deficiencies. Conclusion. These results show that anemia and deficiencies for iron, folic acid deficiency, and vitamin B12 are very common within the first year after LRYGB. We advise a minimal daily intake of 65 mg of iron in male and 100 mg in female patients, 350 μg of vitamin B12, and 400 μg of folic acid. Patients undergoing LRYGB must be closely monitored for deficiencies pre- and postoperative and supplemented when deficiencies occur.